Analisis Penerapan Undang-Undang Nomor 1 Tahun 1974 Juncto Undang-Undang Nomor 16 Tahun 2019 Tentang Perkawinan Terhadap Hak Pembatalan Perkawinan Tanpa Restu Oleh Wali Mujbir - Dewi Sri Puspiana; Muhammad Saleh; Suaib Lubis (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The guardian of the lineage is a role that must be present in a marriage to act as a marriage guardian in marrying off one's daughter. This research discusses marriage annulment due to the marriage guardian not being the biological father with the aim and purpose of this research being to find out about legal tolerance in decisions from the perspective of Islamic law and Indonesian law, and to explain the position of the guardian in the Marriage Law. In this research the author uses normative research which is qualitative in nature, namely research which is descriptive in nature and tends to use analysis whose objects are legal principles, laws, rules, court decisions and doctrine. As well as using a research approach with library research (Library) and field research with data collection techniques. This research concludes that a marriage is invalid if it is carried out by someone who is not a guardian of the lineage or a guardian judge if there is a guardian of the lineage. So if that happens the marriage will be canceled. In the view of Islamic law, canceling a marriage is fasakh, which means broken. The marriage was damaged because of a defect in the marriage process. In Decision Number 1784/Pdt.G/2023/PA.Mdn, it was found that the plaintiff's marriage guardian was his adoptive father, which in Islamic law states that the person who has the right to be the marriage guardian is the nasab guardian. His adoptive father admitted to the KUA that it was true that he was the biological father of the plaintiff and that he did not know the law that if a marriage is not with the guardian of one's lineage, the marriage is annulled because there is a legal defect in it. The judge's decision in this case was correct, because the defendants consisted of the husband, the chairman of the KUA, and witnesses to all the truth that happened. As stated in Article 1925 of the Civil Code: